The Literary Value and Characteristics of Omani Journeys - hassan, Nasreddin Ibrahim; Alsalmi, Haitham Ahmed (Journal of Humanities & Social Sciences, 2021)
This study aims to bring the preciousness and value of the Omani journeys into the spotlight through the exhibition and analysis of a selected collection of poetic writings which are inseparable characteristic of this genre of literature. However, prose was the most common type of literature used by travelers to document their adventures while poetry was predominantly employed by poets. The study also discussed the general traits and artistic features of these poetic pieces and it concluded that: • Travel literature is a form of literature which has unique characteristics and features compared to other genres of literature. • Travelers chose to use simple and clear rather than complicated and weird language to describe their travel experiences and encounters. • The religious influence is clearly visible in the travelers’ artistic style. The Quran and the Sunnah constituted the basis of their culture and the pool of their eloquent and expressive language.